Ochratoxin A 'in vitro' biosynthesis by the Aspergillus ochraceus E'G isolate - Bočarov-Stančić Aleksandra S.; Miljković Aleksandra D.; Resanović Radmila M.; Nešić Ksenija D.; Jaćević Vesna M.; Mihaljčić Danijela N. (Zbornik Matice Srpske za Prirodne Nauke, 2009)
This paper deals with the biosynthetic capacity for ochratoxin A (OTA) production by Aspergillus ochraceus E'G isolate derived from A. ochraceus CBS 108.08 strain, during 2007. Preliminary analysis of fungal potential for the production of OTA were performed according to the modified method of Filtenborg et al. (1983). Toxin production was tested in the following liquid media: (i) glucose-peptone-yeast extract broth (GPY - pH 5.6), (ii) potato-dextrose broth (PDB - pH 6.9), (iii) yeast extract-sucrose broth (YES - pH 6.5), and (iv) YES broth supplemented with 0.23 mg/l ZnSO4 x 5 H2O (YESZn - pH 6.5) after stationary and submerged cultivation. Dynamics of OTA biosynthesis was tested after the cultivation of A. ochraceus E'G on natural solid substrates, such as wet sterilized rice, corn and wheat grain. Cultivations were performed during different time periods (ranging from four days to few weeks) at different temperatures (ranging from 21°C to 30°C). The presence of OTA was determined as follows: (i) in liquid media according to the method of Balzer et al. (1978) modified by Bočarov-Stančić et al. (2003), and (ii) in the solid substrates according to the Serbian official methods for sampling and analyzing of fodder (Official Gazette of SFRY, No. 15/87). After the cultivation of A. ochraceus E'G isolate in liquid media, the highest yield of OTA (6.4 mg/l) was obtained after submerged cultivation in PDB (4 days, 128 rpm, 21-23°C). In the case of cultivation on solid substrates, the highest amount of OTA (800.0 mg/kg of dry matter) was recorded after several week long cultivation on wheat grain at 30±1°C.